2.9k views
22 votes
If you were to use the substitution method to solve the following system, choose the new equation after the expression equivalent to y from the first equation is substituted into the second equation. (1 point) 12x − y = −4 4x − 3y = −6 Group of answer choices 4x − 3(−12x − 4) = −6 4x − 3(12x + 4) = −6 4(12x + 4) − 3y = −6 4(−12x − 4) − 3y = −6

User Liam Gray
by
4.9k points

1 Answer

11 votes

Answer:

4x - 3(12x + 4) = -6

Explanation:

12x - y = -4 ------------(I)

12x = -4 + y

12x + 4 = y --------------(III)

4x - 3y = -6 ------------(II)

Substitute y = 12x + 4 in equation (II)

4x - 3(12x + 4) = -6

User Pgupta
by
5.2k points